2007
DOI: 10.1007/s10571-006-9127-8
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Upregulates and Colocalizes with LGI3 in Cultured Rat Astrocytes

Abstract: 1. The leucine-rich glioma inactivated (LGI) family of genes encodes a leucine-rich repeat (LRR) protein, proteins that are thought to be specifically involved in protein-protein and protein-matrix interactions. Since amyloid beta peptide (Abeta) has been previously shown to induce the expression of another LRR-encoding gene in neural cells, we assessed how Abeta affects LGI gene expression in rat primary cerebral cortical cultures and astrocyte cultures. Both RT-PCR and Western Blotting analyses revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
4
18
0
1
Order By: Relevance
“…2). This is consistent with the result of Kimura et al (2007) that after 24 h of incubation, the increase in GFAP was not significant. However, it should note that Kimura et al used Fischer 344 rats, which is a normal strain of laboratory rat (Holmes 2003).…”
Section: Summary Of Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2). This is consistent with the result of Kimura et al (2007) that after 24 h of incubation, the increase in GFAP was not significant. However, it should note that Kimura et al used Fischer 344 rats, which is a normal strain of laboratory rat (Holmes 2003).…”
Section: Summary Of Resultssupporting
confidence: 92%
“…2), suggesting that astrogliosis induced by Ab might be a prominent event in aging prone astrocytes, while it might be an early or inconspicuous event in normal astrocytes ( Fig. 4 in Kimura et al 2007). In fact, in untreated control cultures, the GFAP level of P8 astrocytes was slightly higher than that of R1 astrocytes (Fig.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that Ab induces the expression of a transmembrane protein that contains leucine-rich repeats (LRRs) (Satoh et al 2002). Using cultured rat astrocytes, we recently showed that Ab upregulates and colocalizes with leucine-rich glioma inactivated (LGI) 3, a transmembrane protein containing LRRs (Kimura et al 2007). …”
mentioning
confidence: 99%